2006
DOI: 10.1007/s00221-006-0499-2
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine-induced neuropathy in rat: electrophysiological and histological study

Abstract: Peripheral sensory-motor neuropathy is one of the most frequent side effects of vincristine (VCR) administration, which often limits its usefulness in the treatment of a wide range of neoplastic diseases. The purpose of this work is to study VCR neurotoxicity in experimental animals from clinical, electrophysiological, and histological points of view. Sixty-five rats were used as a control group and 31 rats were divided into two groups and given VCR in two different regimens: the fixed-dose group (0.2 mg/kg) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 30 publications
2
18
0
1
Order By: Relevance
“…We observed that the amplitude of the MCAP was significantly decreased, while its duration was significantly prolonged in the VCR group. This suggests that a significant number of sensory and motor fibers are affected by the drug as confirmed by reported histological studies, which showed VCR-induced axonal degeneration as well as disorganization of the axonal microtubule cytoskeleton and increase in the caliber of unmyelinated sensory axons (9,16). On the other hand, no significant change was observed in conduction velocity.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We observed that the amplitude of the MCAP was significantly decreased, while its duration was significantly prolonged in the VCR group. This suggests that a significant number of sensory and motor fibers are affected by the drug as confirmed by reported histological studies, which showed VCR-induced axonal degeneration as well as disorganization of the axonal microtubule cytoskeleton and increase in the caliber of unmyelinated sensory axons (9,16). On the other hand, no significant change was observed in conduction velocity.…”
Section: Discussionsupporting
confidence: 66%
“…Inc., Chungcheongnamdo, Korea; 1 mg/mL vial) was injected at a dose of 150 μg/kg, intraperitoneally, three times weekly for five consecutive weeks (8,9); Group III (EPO-treated group 1, EPO1 group), this group of rats was treated with VCR at the same dose and route of administration as in group II and concomitantly received human recombinant EPO (Egyptian International Pharmaceutical Industries Co., 10th of Ramadan City, Egypt; 10,000 IU/mL vial) at a dose of 40 μg/kg, intraperitoneally, three times weekly for five consecutive weeks (7); Group IV (EPO-treated group 2, EPO2 group), this group of rats was subjected to the same treatment protocol as in group III, but the EPO dose was doubled (80 μg/kg).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…After the last behavioural tests, six rats were anaesthetized with pentobarbital sodium (65 mg ⁄ kg). Body temperature was then monitored and maintained within normal limits; then, sensory nerve conduction velocity (SNCV) in the left sural and tail nerve and motor nerve conduction velocity (MNCV) in the left sciatic and tail nerve were recorded as previously described using an isometric force transducer (MLT 1030 ⁄ D; AD Instruments, Power Lab, Oxford, UK) and the same stimulating and recording pin electrodes (pin; AD Instrument) [18].…”
Section: Methodsmentioning
confidence: 99%
“…Vincristine L'existence de cette neuropathie a é té confirmé e chez l'animal par O N C O L O G I E une diminution des vitesses de conduction nerveuses et l'existence d'une dé gé né rescence axonale pure distale ou associé e à une dé myé linisation secondaire [23]. Les deux principaux modè les animaux ont ré vé lé l'existence d'une hyperalgé sie et allodynie mé canique associé es à une hyperalgé sie et allodynie thermique au froid [1,6].…”
Section: é Tudes Pré Cliniquesunclassified